Metabolic Syndrome Among Young Health Professionals in the Multicenter Latin America Metabolic Syndrome Study (2020)
ABSTRACT: Background: Metabolic syndrome (MS) and its components increase the risk of a number of chronic diseases. Evidence regarding its prevalence among health professionals, particularly in Latin America, is limited. The purpose of this study was to assess the overall prevalence of MS and its components among health professionals and students from five Latin American countries. Methods: A cross-sectional multicenter study entitled LATIN America METabolic Syndrome (LATINMETS) was conducted on five groups of apparently healthy volunteer subjects. Sociodemographic factors, lifestyle variables (smoking and physical activity), anthropometric measurements (weight, height, and waist circumference), standard biochemical analyses [triglycerides, glucose, and high-density lipoprotein cholesterol (HDLC)], and blood pressure measurements were assessed. MS was diagnosed based on internationally harmonized criteria. Associations between MS components and sociodemographic, lifestyle, and anthropometric variables were analyzed using multivariate logistic regression. Results: A total of 1,032 volunteers (n = 316-Mexico, n = 285-Colombia, n = 223-Brazil, n = 132-Paraguay, and n = 76-Argentina) were recruited. The majority of them were women (71.9%), students (55.4%), and younger than 28 years (67.2%). The overall prevalence of age-standardized MS was 15.5% (23.1% men and 12.2% women). The majority (59.3%) presented at least one MS component, mainly abdominal obesity (29.7%) and low HDL-C levels (27.5%). After adjusting for age and sex, MS and its components were positively associated with being overweight or obese. Conclusions: MS prevalence in this study was similar to that generally found among young populations in Latin-American countries. More than half of the sample had at least one MS component, suggesting that preventive measures and treatments aimed at achieving low-risk health status are essential in this population.